A retrospective review of the incidence of various complications in different delayed breast reconstruction methods. Issue 1 (2nd January 2016) - Thorarinsson, Andri; Fröjd, Victoria; Kölby, Lars; Lewin, Richard; Molinder, Niclas; Lundberg, Jonas; Elander, Anna; Mark, Hans
Abstract: Background : Breast reconstruction is a common standard procedure in many centres after breast cancer surgery. The aim of the present study was to investigate and compare the incidence of various complications in different reconstruction methods. Method : Six hundred and eighty-five patients were retrospectively classified into five groups: (1) Deep inferior epigastric perforator flap (DIEP), (2) latissimus dorsi flap (LD), (3) lateral thoracodorsal flap (LTDF), (4) expander with secondary implant (EXP), and (5) direct implant (DI). Demographic and perioperative data, the incidence of complications, and follow-up data were collected. Results : There was a significant difference between groups regarding overall early complications ( p  < 0.001). The DIEP group had the highest incidence of overall complications (50.0%) ( p  < 0.05). DIEP also had the highest incidence of fat necrosis (18.3%), skin necrosis (22.1%), and incidence of reoperation for complications (26.9%) compared to the other reconstruction methods. In the entire group of patients, the overall incidence of late complications (occurring >30 days after surgery) that needed surgical corrections was 54.7%. The incidence of late complications was 46.2% for DIEP, 66.4% for LD, 74.8% for LTDF, 44.9% for EXP, and 62.9% for DI. The DIEP group had higher incidences of late local complications (fat necrosis, skin necrosis, haematoma, seroma, and wound rupture combined), and scars requiring treatment than the other reconstruction methods. Conclusion : Meticulous registration of incidence of different complications in five different breast reconstruction methods revealed high complication rates with all methods. The differences in incidence of complications were related to the operation method used. Based on these results, careful individual planning of a breast reconstruction is mandatory.